“Digital Generation”: Threats and Hopes in the Era of Information-Digital Civilization - A. I. Kugay; V. V. Mikhailova (Управленческое консультирование)
The article refers to the information and digital civilization — its threats and hopes formed by it to the “digital generation”. On the one hand, an identifier is the name of a managed object in a digital society. Each step of the “digitized citizen” can be checked, serve as a test of loyalty to the system, to agree with the worldview and ideological attitudes adopted in it. Civilization atrophies and deforms auditory and visual physiological analyzers, changes mental features of the younger generation. On the other hand, young people, like the Pythagoreans who offered us the digital Universe, perceive the digitalization of social life organically as integration into the natural environment of life. Information and digital civilization gives birth to the world society as an alternative site of politics, differs from the main international society, creates its own logic of communication, mobilization and action. If international diplomacy creates a formal, hierarchical, formal and exclusive atmosphere concerning the events of intergroup relations, transnational digital network (TDCN) are informal, egalitarian, highly inclusive and open to multilingual presentation and alternative forms of political expression. Information and digital civilization creates limitless conditions for the development of human ability to foresee and foresee the future, and not a prophet, not a magician, not a psychic, and the most common, the average person. After all, our mind develops faster than the body, which creates the preconditions for the fact that humanity, which has become a digital community, will be able to abandon the harmful “benefits” of civilization without becoming a victim.